2002
DOI: 10.1016/s0735-1097(01)01710-7
|View full text |Cite
|
Sign up to set email alerts
|

Relative expression of immunolocalized connexins 40 and 43 correlates with human atrial conduction properties

Abstract: In human right atrium, conduction velocity is inversely related to immunodetectable Cx40 levels. The relative level of connexins 40 and 43 signal is strongly associated with atrial conduction properties, suggesting that interactions between the two connexins may result in novel coupling properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
87
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 28 publications
9
87
0
Order By: Relevance
“…14,16,17 Controversial reports have also been published about Cx40 remodeling, expression being upregulated in chronic human AF 16,18 or downregulated in a heterogeneous pattern in goats and humans. 14,17,19,20 Kanagaratnam et al 21 showed a strong correlation of electrical propagation velocity with the ratio of Cx43 (or Cx40) to total Cx immunosignal ([Cx43ϩCx40]). Thus, Cx43/[Cx43ϩCx40] was directly and Cx40/[Cx43ϩCx40] inversely related to propagation veloc-ity.…”
mentioning
confidence: 99%
“…14,16,17 Controversial reports have also been published about Cx40 remodeling, expression being upregulated in chronic human AF 16,18 or downregulated in a heterogeneous pattern in goats and humans. 14,17,19,20 Kanagaratnam et al 21 showed a strong correlation of electrical propagation velocity with the ratio of Cx43 (or Cx40) to total Cx immunosignal ([Cx43ϩCx40]). Thus, Cx43/[Cx43ϩCx40] was directly and Cx40/[Cx43ϩCx40] inversely related to propagation veloc-ity.…”
mentioning
confidence: 99%
“…Heteromeric means that a single connexon may be composed of different connexins such as Cx40 and Cx43 in atria, and coupled to another connexon comprised of different connexins. Cx40 and Cx43 colocalize in intercalated disks between atrial myocytes [48,54]. These two proteins have been demonstrated to interact in the formation of heteromeric/heterotypic gap junction channels in vitro [55,56].…”
Section: Structure and Function Of Gap Junctionsmentioning
confidence: 99%
“…Such remodeling might be the result of fibrosis that disrupts normal gap junction connections. Although fibrosis has not been found to be associated with all pathological causes of atrial fibrillation [48], fibrosis on a microscale might not always be recognized with standard histological techniques. It invariably occurs with aging in the form of fine longitudinally oriented collagenous microsepta [59].…”
Section: Remodeling Of Intercellular Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, the autonomic nervous system has a crucial role in the genesis, maintenance and abruption of atrial fibrillation (Duffy& Wit, 2008;Sandres et al,2004), and there is a fat pad localized in superior vena cava and the root of aorta as the origin of cardiac nerve, being called SVC-Ao fat pad (Kapa et al,2010;Volders ,2010;Ji et al,2010). The mechanism of atrial fibrillation involves multiple effects (Chiou et al,1997;Tsuboi et al,2000;Hoffmann et al, 2006;Haissaguerre et al1998;Wit & Boyden,2007), the expression of connexins is changed and is associated with increased propensity for arrhythmias (Kanagaratnam et al, 2002, Herve et al, 2007, Stergiopoulos et al, 1999, Verheule S et al, 2002, Kanagaratnam et al, 2007Valiunas et al,2001;Cottrell et al,2002;Elenes et al,1999). Pulmonary veins and left atria are the primary structure of genesis, persistence of atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%